If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying -3c = -4c + -7 Reorder the terms: -3c = -7 + -4c Solving -3c = -7 + -4c Solving for variable 'c'. Move all terms containing c to the left, all other terms to the right. Add '4c' to each side of the equation. -3c + 4c = -7 + -4c + 4c Combine like terms: -3c + 4c = 1c 1c = -7 + -4c + 4c Combine like terms: -4c + 4c = 0 1c = -7 + 0 1c = -7 Divide each side by '1'. c = -7 Simplifying c = -7
| -3-10b=-9b | | 20x=4.04 | | 20x=.0404 | | .0404x=20 | | z/10-6=1 | | -12=-3(b+11) | | 81-31/5= | | h+3h+4=20 | | 65x=91 | | 3k+-16k+-2=11 | | Y=5x^2+2x | | 490x^2+71x-113=0 | | x-2x+3x=18 | | 7n-4n-2=7 | | 6g-2g-2=18 | | y/3-7=4 | | 4p-2p=12 | | 80x=112 | | .14x=7 | | (100x^2)/(4x^4) | | -5g-7g+-7=17 | | 8j-4j=8 | | 11k+4=37 | | 14x^2-6x-10=0 | | 6+8+x=10+6 | | 2-x=-13x-100+3(2-x) | | .97x=233 | | 6r-8=10 | | .03*x=7 | | 8+y-y=8 | | 5x+2=(5-x)+2 | | 9+5y=22 |